2015
DOI: 10.1007/s11255-015-1074-1
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional hyaluronic acid: an innovative treatment for Peyronie’s disease

Abstract: Considering the minimally invasive approach in this study, the absence of major side effects, and the significant treatment outcomes achieved, we conclude that intralesional penile injections with HA are effective for treating Peyronie's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…Currently, Xiaflex it is the only drug available for treatment of Peyronie's disease (Gelbard et al, 2013). Similar results were reported by another study including 83 patients who underwent treatment with HA vs. 81 patients in the control group (Gennaro et al, 2015). In addition, therapy with collagenase is limited by the high cost.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Currently, Xiaflex it is the only drug available for treatment of Peyronie's disease (Gelbard et al, 2013). Similar results were reported by another study including 83 patients who underwent treatment with HA vs. 81 patients in the control group (Gennaro et al, 2015). In addition, therapy with collagenase is limited by the high cost.…”
Section: Discussionsupporting
confidence: 59%
“…For this reason novel intralesional agents are strongly needed with better benefit-risk profile. Recent prospective, multicenter, pilot study assessing the efficacy of hyaluronic acid (HA) as intralesional treatment for patients with PD showed encouraging preliminary results for improvement of plaque size, penile curvature, and overall sexual satisfaction (Zucchi et al, 2016) and similar results are reported in other study (Gennaro et al, 2015). Hyaluronic acid is an extracellular matrix glycosaminoglycan that at physiological pH is highly polarized and maintains hydration, turgor, plasticity and viscosity in the amorphous connective tissue matrix.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Two retrospective studies and a more recent prospective study have shown a reduction in penile plaque size and curvature, as well as improved penile rigidity. [52][53][54] Botulinum toxin has been shown to reduce fibrosis and scarring. A single study evaluated botulinum toxin A as a treatment for PD and has shown a positive response for safety and improvement in penile curvature, while data from further investigations is pending.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…More recently, some research groups have evaluated the potential role of HA as a treatment for PD. In a retrospective study of 83 carefully selected patients, Gennaro et al [46] found a significant reduction in penile plaque size and curvature, as well as improved penile rigidity A more recent prospective study of 65 patients likewise demonstrated improvement across all PD domains and reported no major complications [47]. HA is a promising novel therapy for PD that appears to have some efficacy in improving PD symptoms, but data comparing HA treatment to placebo or alternative therapies are lacking.…”
Section: Intralesional Therapiesmentioning
confidence: 99%